Unexpectedly Diverse Mesorhizobium Strains and Rhizobium leguminosarum Nodulate Native Legume Genera of New Zealand, while Introduced Legume Weeds Are Nodulated by Bradyrhizobium Species - Weir, Bevan S. (American Society for Microbiology, 2004)
The New Zealand native legume flora are represented by four genera, Sophora, Carmichaelia, Clianthus, and Montigena. The adventive flora of New Zealand contains several legume species introduced in the 19th century and now established as serious invasive weeds. Until now, nothing has been reported on the identification of the associated rhizobia of native or introduced legumes in New Zealand. The success of the introduced species may be due, at least in part, to the nature of their rhizobial symbioses. This study set out to address this issue by identifying rhizobial strains isolated from species of the four native legume genera and from the introduced weeds: Acacia spp. (wattles), Cytisus scoparius (broom), and Ulex europaeus (gorse). The identities of the isolates and their relationship to known rhizobia were established by comparative analysis of 16S ribosomal DNA, atpD, glnII, and recA gene sequences. Maximum-likelihood analysis of the resultant data partitioned the bacteria into three genera. Most isolates from native legumes aligned with the genus Mesorhizobium, either as members of named species or as putative novel species. The widespread distribution of strains from individual native legume genera across Mesorhizobium spp. contrasts with previous reports implying that bacterial species are specific to limited numbers of legume genera. In addition, four isolates were identified as Rhizobium leguminosarum. In contrast, all sequences from isolates from introduced weeds aligned with Bradyrhizobium species but formed clusters distinct from existing named species. These results show that native legume genera and these introduced legume genera do not have the same rhizobial populations.